Optimal Design and Experimental Verification of Heat Transfer Capacity of Heat Exchanger of in Large Temperature Difference Air Handling Unit - Xu Yanni; Zhuo Mingsheng; Zhang longai; He Weiguang (Zhileng xuebao)
A chilled water system with large temperature difference is essential for the economical operation of air conditioning. This design also enables air handling units (AHU) to achieve an energy-saving effect. Based on the mechanism of the heat exchange in AHU, this study analyzes how chilled water with large temperature difference affects the heat transfer of AHU. Experiments are conducted to test the influence of large temperature difference of chilled water in the cooling coils with differential enthalpy method. The pipe shapes and flow routes are optimized. The performances of the cooling coils are compared for different coil pipe shapes, flow routes, and fin spacings. Using the same heat exchange section, the AHU of this design reduces the energy consumption by approximately 20% compared with a conventional unit. Furthermore, a preferable scheme is proposed to reduce energy consumption by 25%, in which cooling coils are composed of four-row high-efficiency inner threaded pipes that have the same ratio (cooling capacity to airflow) as those of six-row non-threaded pipes. The results provide applicable and practical cases for the design of AHU with large temperature difference.